2020
DOI: 10.1109/lawp.2020.2975143
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Selective Surface Coded Retroreflectors for Chipless Indoor Localization Tag Landmarks

Abstract: This letter presents the integration of frequency selective surfaces (FSSs) with retroreflectors for the realization of chipless wireless indoor localization tag landmarks. As an example, the high radar cross section (RCS) of a trihedral corner reflector is signed with an FSS-based stopband filter, so that the backscattered power from several corner reflectors can be distinguished by a mobile reader according to the frequency response of the FSS. Measurement results with a 3 × 3 × 3 cm 3 trihedral corner refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…From the previous comparison, it can be concluded that the highest RCS is achieved by the trihedral cubical corner reflector. Coding in corner reflectors can be achieved by frequency selective surfaces [6], dielectric resonators [7], or thin film modulators [8] with high RCS for applications such as indoor localization. Similarly, coding in flat plate reflectors can be achieved by a frequency selective surface plate, a planar dielectric resonator array in front of a metal plate [9], or microstrip coding [10], but this type of reflectors share the abrupt RCS decay for directions other than broadside of the flat metal reflector.…”
Section: A Metallic Retroreflectorsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the previous comparison, it can be concluded that the highest RCS is achieved by the trihedral cubical corner reflector. Coding in corner reflectors can be achieved by frequency selective surfaces [6], dielectric resonators [7], or thin film modulators [8] with high RCS for applications such as indoor localization. Similarly, coding in flat plate reflectors can be achieved by a frequency selective surface plate, a planar dielectric resonator array in front of a metal plate [9], or microstrip coding [10], but this type of reflectors share the abrupt RCS decay for directions other than broadside of the flat metal reflector.…”
Section: A Metallic Retroreflectorsmentioning
confidence: 99%
“…where r denotes the relative permittivity and R is the radius of the lens. The monostatic RCS of the retroreflective Luneburg lens at the boresight can be calculated by equation (6).…”
Section: B Retroreflective Luneburg Lensmentioning
confidence: 99%
See 2 more Smart Citations
“…A simpler and very efficient alternative to the above corner reflector design was found by adopting a concept [25], first demonstrated using a stopband frequency selective surface (FSS) based on conductor patterns (crossed dipoles) as depicted in Fig. 5.…”
Section: Introductionmentioning
confidence: 99%